Pengaruh Posisi dan Tipe Ventilasi Kemasan Peti Karton (Corrugated Box) terhadap Mutu Buah Manggis Selama Proses Transportasi dan Penyimpanan - Yulianti, Ni Luh; Aviantara, I Gusti Ngurah Apriadi; Kencana, Pande Ketut Diah (Jurnal BETA (Biosistem dan Teknik Pertanian), 2025)
The aim of this research was to acquire packaging that can uphold the quality of mangosteen fruit while being transported and stored. A Randomized Group Design Factorial method was used, where the first factor is the location of ventilation and the second factor is a combination of ventilation types. The first factor comprises two levels, specifically, the center location of the packaging surface (L1) and a uniform distribution on the surface of the packaging (L2). The second factor comprises three levels: completely round type (V1), completely oval type (V2), and a combination of oval and round (V3). The ventilation dimension for all treatments was 3.45% of the total packaging area. Each treatment was replicated three times. A 5 kg capacity corrugated carton of dimensions 27 cm x 22 cm x 22 cm in the full-flap type was utilized for packaging, with the fruit arranged in the Face Centered Cubic type. Packaging tests were conducted by transporting mangosteen fruits in packaging through the city and on poorly surfaced roads. The testing parameters comprised the determination of packaging's compressive strength, the distribution of temperature within the packaging, the total soluble solids value of the fruits, the pH value of the fruits and the percentage of weight loss. The obtained data were analysed by analysis of variance and if there was an effect of treatment on the observed parameters, the Duncan test was applied. The test results highlight the significant impact of treatment interaction on mangosteen fruit quality parameters including weight loss, TPT, and fruit pH. The packaging design measured at 27cm x 22cm x 22cm demonstrated a compressive strength value of 284 kgf. The treatment which produced the lowest weight loss of 2.30%, a TPT value of 15.30 and pH 2.6, is L1V1. This treatment is optimal for packaging mangosteen fruit, as it is able to maintain the fruit's quality.